2018
DOI: 10.1016/j.molcel.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

MICU1 Interacts with the D-Ring of the MCU Pore to Control Its Ca2+ Flux and Sensitivity to Ru360

Abstract: SUMMARY Proper control of the mitochondrial Ca2+ uniporter’s pore (MCU) is required to allow Ca2+ dependent activation of oxidative metabolism and to avoid mitochondrial Ca2+ overload and cell death. The MCU’s gatekeeping and cooperative activation is mediated by the Ca2+ sensing MICU1 protein, which has been proposed to form dimeric complexes anchored to the EMRE scaffold of MCU. We unexpectedly find that MICU1 suppresses inhibition of MCU by ruthenium red/Ru360, which bind to MCU’s DIME motif, the selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 32 publications
7
105
1
Order By: Relevance
“…Working model for the heterodimer of MICU1-MICU2 regulates Ca 2+ uptake Previous work indicated that the association between the MICU1-MICU2 complex and MCU is Ca 2+ -dependent. At low Ca 2+ concentrations, the MICU1-MICU2 complex binds to the D-ring of MCU [24,25]. Increasing Ca 2+ concentrations induce a conformational change in the MICU1-MICU2 heterodimer and its release from MCU [23].…”
Section: Of 13mentioning
confidence: 99%
“…Working model for the heterodimer of MICU1-MICU2 regulates Ca 2+ uptake Previous work indicated that the association between the MICU1-MICU2 complex and MCU is Ca 2+ -dependent. At low Ca 2+ concentrations, the MICU1-MICU2 complex binds to the D-ring of MCU [24,25]. Increasing Ca 2+ concentrations induce a conformational change in the MICU1-MICU2 heterodimer and its release from MCU [23].…”
Section: Of 13mentioning
confidence: 99%
“…Thus, mitochondrial Ca 2+ uptake must be tightly controlled, but how mitochondrial Ca 2+ uptake through MCU is regulated is controversial (2,3). The MCU channel in metazoans exists as a protein complex comprised of MCU as the tetrameric channel pore-forming subunit (4,5), EMRE, a single-pass transmembrane protein that is essential for channel activity (6)(7)(8), and IMS-localized (but see (9)) Ca 2+ -binding EF hand domain-containing MICU1/2 heterodimers (10-13) that associate with the channel complex by interactions with the carboxyl-terminus of EMRE (14) and with MCU (15,16). In a current model of MCU regulation (but see (2)), MICU1/2 promotes cooperative channel activation in response to Ca 2+ binding by their EF hands, whereas apo-MICU1/2 imposes a threshold [Ca 2+ ]i below which MCU channel activity is inhibited, so-called channel gatekeeping (13,(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Ca 2+ ] and buffering capacity, allowing for enhanced cellular regulation of mitochondrial Ca 2+ homeostasis. Recent studies have demonstrated a direct biochemical interaction of MICU1/2 with the MCU selectivity filter(15, 16). Because mutations in either MCU or MICU1 that disrupt this interaction lead to a constitutively open channel, it has been suggested that MICU1/2 functions as a classic pore blocker (16).…”
mentioning
confidence: 99%
“…However, only partial restoration to WT levels can be achieved in the MCU OE model by pharmacologically inhibiting MCU. This could be due to factors other than mitochondrial Ca 2+ uptake being affected in the MCU OE model (such as ER Ca 2+ levels), insufficient permeability of Ru360 into cells, or an abundance of MICU1/MICU3 which can block Ru360 binding to MCU (Paillard et al, 2018).…”
Section: Discussionmentioning
confidence: 99%